2017
DOI: 10.1186/s12877-017-0455-y
|View full text |Cite
|
Sign up to set email alerts
|

Association among activities of daily living, instrumental activities of daily living and health-related quality of life in elderly Yi ethnic minority

Abstract: BackgroundThe health-related quality of life (HRQoL) of the elderly population of Yi ethnic minority, which is the seventh largest nationality in China, has been rarely reported. This study was designed to explore the HRQoL of the elderly Yi ethnicity and association between their HRQOL and functional abilities.MethodsA total of 291 Yi ethnic residents were randomly recruited from 12 rural counties in Yunnan province and divided into different age groups. Local residents in Yunnan province and the elderly from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
37
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 25 publications
6
37
2
3
Order By: Relevance
“…Most of the previous studies found that lower education [9,11], increased age [10,11], and multimorbidity [3,16,17] were related to poor functional ability. Meanwhile, the role of social capital in elderly health have been noted from multiple studies [22,46].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most of the previous studies found that lower education [9,11], increased age [10,11], and multimorbidity [3,16,17] were related to poor functional ability. Meanwhile, the role of social capital in elderly health have been noted from multiple studies [22,46].…”
Section: Discussionmentioning
confidence: 98%
“…found that the prevalence of functional disability among older people ranged from 16.2% in China to 55.7% in India [8].Greater attention has been paid to exploring the correlates concerning the health and well-being of older adults [9]. Previous studies from China and abroad have both found that advanced age [10,11], frailty [12,13], depression [14] underweight or obesity, physical inactivity, a poor self-rated health, less engagement in level social activities, and pain [15] were most commonly associated with the incidence of ADL or IADL disability. Furthermore, many studies have identified that comorbidity accelerated the decline of functional ability of the elderly [3,11].…”
mentioning
confidence: 99%
“…The Lawton IADL is an appropriate instrument with eight categories to assess independent living skills [33]. It has been used and proven in the Chinese population with a satisfactory Cronbach's alpha of 0.739 [34]. The SSRS was developed in China and is widely used with high validity (Cronbach's alpha 0.83 to 0.90) and reliability (test-retest reliability 0.92) [35,36].…”
Section: Functional Ability: This Outcome Will Be Measuredmentioning
confidence: 99%
“…IADL were measured by employing the Instrumental Activities of Daily Living Scale (IADL) (5), which includes a range of higher-level activities that are considered to address the older adult's capacity to interact with his or her community (10). The scores of this scale range from 0 to 8, with 0 being the least independent and 8 being the most independent in the eight-item scale (5,11,12).…”
Section: Measurement Instrumentsmentioning
confidence: 99%